Handbook of nursing diagnosis - Carpenito-Moyet, Lynda Juall (Philadelphia : Wolters Kluwer/Lippincott Williams & Wilkins Health, 2013)
" The ideal quick reference, this handbook offers practical guidance on nursing diagnoses and associated care. Sections cover Nursing Diagnoses, Health Promotion/Wellness Nursing Diagnoses, and Diagnostic Clusters--medical conditions with relevant collaborative problems and nursing diagnoses. The newest nursing diagnoses approved by NANDA International for 2012-2014 are included"--
"This handbook is the ideal quick reference to nursing diagnoses and collaborative problems authored by the foremost authority on NANDA International diagnoses. The practical, easy-access format helps you reach accurate nursing diagnoses with speed and confidence. Sections cover nursing diagnoses, health promotion and wellness diagnoses, collaborative problems, and diagnostic clusters"--
Includes bibliographical references (p. 847-859) and indexes.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2022. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Nursing diagnosis -- Handbooks, manuals, etc; Nursing Diagnosis; Electronic books